Noncanonical roles of p53 in cancer stemness and their implications in sarcomas - Curylova, Lucie; Ramos, Helena; Saraiva, Lucília; Skoda, Jan (Cancer letters, 2022)
Impairment of the prominent tumor suppressor p53, well known for its canonical role as the "guardian of the genome", is found in almost half of human cancers. More recently, p53 has been suggested to be a crucial regulator of stemness, orchestrating the differentiation of embryonal and adult stem cells, suppressing reprogramming into induced pluripotent stem cells, or inhibiting cancer stemness (i.e., cancer stem cells, CSCs), which underlies the development of therapy-resistant tumors. This review addresses these noncanonical roles of p53 and their implications in sarcoma initiation and progression. Indeed, dysregulation of p53 family proteins is a common event in sarcomas and is associated with poor survival. Additionally, emerging studies have demonstrated that loss of wild-type p53 activity hinders the terminal differentiation of mesenchymal stem cells and leads to the development of aggressive sarcomas. This review summarizes recent findings on the roles of aberrant p53 in sarcoma development and stemness and further describes therapeutic approaches to restore normal p53 activity as a promising anti-CSC strategy to treat refractory sarcomas.
Keywords: Tumor Suppressor Protein p53; Soft Tissue Neoplasms; Sarcoma; p53-targeted therapy; mezenchymální kmenové buňky; Neoplasms; nádory; Cancer stem cells; lidé; buněčná diferenciace; Mesenchymal Stem Cells; sarkom; Mesenchymal stem cells; Neoplastic Stem Cells; nádorový supresorový protein p53; p53; Cell Differentiation; nádory měkkých tkání; nádorové kmenové buňky; Humans